Intelligent automated amplification for data acquisition systems - Goh, Benjamin Chong Chuan. (2011)
Data Acquisition Systems are used in a whole wide range of hardware and software applications for testing, monitoring and controlling by analog or digital sensing devices such that the acquired data can be stored or processed by a computer. In order to improve the quality of the signal, the data is fed to a signal conditioning circuit before being sampled into digital values. Subsequently, the signal condition is manually observed and evaluated. The project was proposed to implement a data acquisition system with the capability of amplifying the continuous collective data and adapting to changes in amplification when the amplified signal exceeds the maximum peak voltage of the system. The project also targets at the development of hardware integration with Cypress CY8C38 Microcontroller, which can be applied as a core basis for further development of a fully-functional adaptive amplification for various applications such as volcanic seismic and gas sensing, sound and pressure sensing, and electronic circuit applications.